Violation-based Feature Selection for Isolation Forest - Dissanayake, D.M.; Navarathna, R.; Viswakula, S. (University of Colombo, 2024)
Anomaly detection is crucial in sectors like finance and healthcare to identify deviations from normal behavior. The Isolation Forest (ISF) algorithm, introduced by Liu et al. (2008), is effective but has limitations, such as bias towards correlated variables and suboptimal results with irrelevant features. This study introduces the Violation Features Based Isolation Forest (VFIF) algorithm, ...
Keywords: Isolation Forest; Anomaly Detection; Rule Violation